Methodology for validation of electric power system simulation tools; Innovative Smart Grid Technologies Conference Europe (ISGT-Europe), 2017 IEEE PES - Suvorov A. A. Aleksey Aleksandrovich; Andreev M. V. Mikhail Vladimirovich; Ruban N. Yu. Nikolay Yurievich; Ufa R. A. Ruslan Alexandrovich (2018, 2018)
Title screen